Conclusions and implications for policy, practice, and research - Mwangi, Esther; Markelova, Helen; Meinzen-Dick, Ruth S. (University of Pennsylvania Press, 2011)
In this concluding chapter we turn from a detailed analysis of the findings from the studies collected here to the contributions they make to the literature on their respective themes in terms of the way that collective action and property rights can facilitate poverty reduction. Recognizing that conducting these nine studies was just one step in this task, we also consider the open questions that the studies have brought forth for future research and propose the implications that these findings can have for policy and practice. We first discuss the findings in terms of the five themes of the volume and then highlight some contributions that the studies make to the broader literature on collective action and property rights, then end with broader implications for policy, practice, and research.